PERAN MASYARAKAT PESISIR DALAM PENERAPAN STRATEGI KONSERVASI SUMBERDAYA LAUT (KASUS DI KELURAHAN PALABUHANRATU, KECAMATAN PALABUHANRATU, KABUPATEN SUKABUMI) - Winata, Adi; Yuliana, Ernik (LPPM Universitas Terbuka, 2010)
This article is objected to measure the coastal communities role in the implementation of marine resource conservation strategies. The population were all coastal communities in Palabuhanratu, Sukabumi. Respondents of 50 people were chosen randomly. Data were collected by using survey method, and were analyzed by Pearson correlation. The results indicated that the level of education of coastal communities was a primary school. Respondents have been working more than 10 years. Those who knew the meaning of the protection and conservation of marine resources was 56%, while 88% of them did not know the meaning of preservation of marine resources. The role of coastal communities in aspects of marine resource protection was low, in the aspects of marine resource conservation was high, and in the preservation of marine resources was low. The characteristics of coastal communities correlated positively with the level of knowledge of coastal communities (0,3 and ? = 0,05). Furthermore, the level of knowledge of coastal communities associated with the role of coastal communities in the implementation of conservation strategies (0,5 and ? = 0,05).